ANALYZING THE EFFECTIVENESS BILLINGUAL EDUCATION PROGRAMS IN PROMOTING ENGLISH PROFICIENCY AMONG MULTILINGUAL STUDENTS - Samiyeva Nazokat Olim qizi; Eshonqulova Sarvinoz Yashinovna (TADQIQOTLAR, 2026)
ABSTRACT   Bilingual  education  programs  play  an  important  role  in  supporting  English language  development  among  multilingual  students.  These  programs  use  both  the native language and English  as mediums of instruction to help learners understand academic  content  while  improving  their  language  skills.  This  study  analyzes  the effectiveness  of  bilingual  education  programs  in  promoting  English  proficiency, focusing on students’ development in reading, writing, speaking, and listening. It also highlights  key  teaching  strategies  such  as  code-switching,  translanguaging,  and scaffolded  instruction  that  support  language  learning  in  bilingual  classrooms.  The study concludes that well-implemented bilingual education programs can significantly enhance English proficiency and academic performance among multilingual learners.